(untitled) (Zia e Tahqeeq, 2025)
Dawah i.e. preaching of Islam is one of the collective obligations upon Muslims. To convey the message of Allah to humanity Muslims have always been engaged in Dawah activities with different strategies which mainly depended on the situation of the audience. Quran and Hadith draw guidelines for Dawah workers, one of them is to take care audience’s physical and mental situation. Without a caring audience, Dawah’s process could not achieve its objectives. The prospect has been changed about Dawah and this paper deals with Dawah strategies by focusing on multiple audiences of Dawah. This paper will provide guidelines for dawah workers of modern times with special reference to audiences with multiple prospects.